Penilaian Track Quality Index Jalan Rel Rancaekek – Haurpugur - Yusup Fikria Erdiana; Athaya Zhafirah (Institut Teknologi Garut, 2023)
Railway traffic will continue to increase by industrial developments, which can affect the geometric conditions of the track, causing a decrease in the quality of the track. The geometric parameters affecting the decline in railroad quality include lift, listing, elevation, and gauge width. The track quality assessment indicator is the Track Quality Index (TQI). This research was conducted to analyze the quality of the railroad based on the TQI value by the Indonesian Railway Standards on the Rancaekek – Haurpugur railroad. The analysis consisted of parameter analysis of the TQI value and multiple linear regression analysis to determine the relationship between lift, listing, spur width, and height measurement parameters with the TQI value. Based on an analysis by the Indonesian Railways Standards, an assessment of the Rancaekek – Haurpugur KM rail road resulted. 175+000 – KM 177+100 falls into category II, which is good. Lift, spur width, listing, and height strongly influence the TQI rating of 92.7%. The parameter that has the most significant influence is the height of 94.1%.